Public resources distribution and CSOs in Brazil: is there a geolocation bias? - Bandeira, Julia Barreto Leite (2022)
The access to financial resources is critical to the maintenance and growth for civil society organizations, that is the reason why many people study ways to boost fundraising for social organizations with the objective to foster development through access to resources. Regulatory changes and societal demands have helped the expansion of resources distributions in Brazil. Our contribution to literature is based on two pillars. First, we expanded the large body of research that defined civil organizations in Brazil and focused geographic inequality based on their definition in the country. Second, we provided exploratory research of the IPEA's Civil Society Map by crossing data between the organization's resources provided by public partnerships, the organization's base location and its founder/leader's proclaimed gender. Through the literature and data analysis we were able to find a correlation on geolocation are correlated is resource distribution through public entities in Brazil, and we suggest what can be done for an inclusive ecosystem. In this context this study plans to suggest several propositions for future research.